1979
DOI: 10.1063/1.91126
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductive imaging using hydrogenated amorphous silicon film

Abstract: Highly resistive hydrogenated amorphous-silicon film has been fabricated and examined as blocking-type photoconductive target of a vidicon-type image pickup tube. The results indicate that this novel silicon vidicon has many advantages over conventional ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Interest in hydrogenated amorphous silicon (a-Si:H) has been greatly increased by the suitability of a-Si:H for the fabrication of low-cost solar cells [1] and large area photodetectors [2]. The large absorption coefficient of a-Si in the visible spectral range has made this material very attractive for solar cell applications.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in hydrogenated amorphous silicon (a-Si:H) has been greatly increased by the suitability of a-Si:H for the fabrication of low-cost solar cells [1] and large area photodetectors [2]. The large absorption coefficient of a-Si in the visible spectral range has made this material very attractive for solar cell applications.…”
Section: Introductionmentioning
confidence: 99%
“…For the photovoltaic detector, the heterojunction gives the device excellent response speed and broadband detection range, but the multilayer structures effectively increase the device cost [14]. For the single-component photoconductive device, the indirect band gap structure makes the device suffer from slow response speed and little photocurrent [15]. Therefore, the silicon-based photoconductor with a suitable heterojunction will satisfy both sides.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is well known that in a-Si, electron multiplication occurs under a high electric field. [19][20][21] It was expected that efficiency would be further improved by adding the electron multiplication effect in DC-EL devices. In this study, whether a-Si shows multiplication under photoexcitation was confirmed, and we discuss the possibility of further efficiency improvement.…”
Section: Introductionmentioning
confidence: 99%